KEWARGAAN DALAM TEORI ISLAM PESANTREN: TRADISI SOSIAL DAN PRAKTIK KEHIDUPAN KEWARGAAN MASYARAKAT PESANTREN - Moh. Ali Mahdi; Hariyanto; Ach. Maimun; Muhammad Afan; Atiqur Rahman Binuri Ramadan (STAI Nusantara Kota Banda Aceh, 2026)
This article examines the concept of citizenship (muwathanah) within Islamic pesantren theory and its practice in the social tradition of pesantren communities in Indonesia. Prior studies on Islamic citizenship largely remain at the normative-theoretical level of fiqh siyasah, while pesantren studies typically focus on character education without framing it as a citizenship practice; this article addresses that gap by using fiqh siyasah categories as an analytical lens to read the social practice of pesantren life. Using a qualitative library-research method, the study finds that pesantren function as a social laboratory that internalises Islamic citizenship values through traditions such as bahtsul masail and the three-tiered brotherhood (ukhuwah islamiyah, wathaniyah, and basyariyah), together with national-insight education. Based on these findings, the article proposes the Pesantren Muwathanah Framework, a conceptual model linking theological grounding, the relational structure of ukhuwah, the space of internalisation within pesantren, and the space of dissemination by alumni into wider society. The study recommends strengthening a citizenship curriculum grounded in pesantren values as a model for religious moderation and social capital building in Indonesia.